Bidirectional Intimate Partner Violence Among Chinese Women: Patterns and Risk Factors - Hu, Ran (Journal of interpersonal violence, 2021)
Bidirectional intimate partner violence (BIPV) refers to the co-occurrence of violence perpetration by both partners. BIPV has been analyzed using samples from different sociodemographic contexts but has yet to be fully explored in China. The present study employed a latent class approach to identify BIPV patterns, rates of prevalence, and associated risk factors among a sample of 1,301 heterosexual adult women in mainland China. Five distinct patterns of BIPV were identified, including (a) bidirectional psychological aggression, (b) bidirectional violence of all types, (c) multi-type victimization with psychological aggression, (d) minimal violence, and (e) bidirectional multi-types without physical violence. Marital status, education, employment status, acceptance of male dominance, and justification of intimate partner violence (IPV) were found to be predictive of different types of BIPV. Our findings suggest a need for a conceptual recognition of the heterogeneity and bidirectionality of IPV among Chinese women. Future research should extend to other diverse populations and sociocultural or clinical contexts in China. IPV assessments, research, and social programs ought to recognize the complexity of IPV and consider various IPV patterns specific to heterosexual women.